Hubungan antara Kompensasi dengan Komitmen Organisasi Guru Sekolah Menengah Pertama Swasta di Kecamatan Pulo Gadung - Tri Sulistyo Jati Mukarrom; Neti Karnati; Winda Dewi Listyasari (Program Studi Manajemen Pendidikan, 2017)
This study aims to determine the relationship between compensation andorganizational commitment junior high school teachers in the district Pulo Gadung. Theresearch approach is a quantitative approach to the method used survey methods. Thisstudy uses correlational study analysis. The study population was Junior highschoolteachers in the district Pulo Gadung with the sample amounted to 79 teachers. Samplingwas done randomly by using simple random sampling with data collection using thequestionnaire. It can be concluded that there is a relationship between compensation andorganizational commitment. This means that the higher the compensation it will furtherenhance the organization's commitment junior high school teachers in the district PuloGadung.